Reassessing the Palermo Protocol: Emerging Gaps in Prevention, Protection and Prosecution in the Digital and Conflict Era - Mbella, Ph.D, Ndinge Nadia (Law and Economy, 2026)
Trafficking in Persons (TIP) remains one of the most heinous transnational crimes that have evolved within the digital and conflict-driven landscape. The United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons Especially Women and Children (the Palermo Protocol), constitutes the primary international legal instrument in the fight against TIP. While the Protocol establishes a tripartite framework of prevention, protection and prosecution, emerging global realities have exposed significant gaps hindering its effectiveness. This study adopts a qualitative research methodology and a doctrinal method to reassess the Protocol in light of contemporary trafficking dynamics. It argues that despite the Protocols contribution to the harmonisation of legal trafficking definitions and its influence in the development of national anti-trafficking laws, digitalisation, armed conflicts and displacements have revealed structural gaps. The study suggests that the Palermo Protocol is outdated as it was initially designed for a state-centric system focused primarily on physical forms of trafficking. In contrast, contemporary trafficking is increasingly transnational, technologically-facilitated and embedded within conflict situations. The paper concludes that while the Protocol remains foundational, it requires substantial normative and institutional strengthening to meet the current digital and conflict related trafficking. The study therefore recommends the adoption of supplementary guidelines to address technology-facilitated trafficking, legal responses to conflict-related exploitation and the adoption of a more adaptive, victim-centered approach capable of capturing emerging forms of trafficking.